1907 Ark. Acts 810 - (:unkn) unknown (My University, 1907)
Prohibited aiding and abetting of every person who shall draw a pistol, gun, or other deadly weapon upon any other person or shall serve or give notice either verbal or in writing to any other person or shall place notice upon the door or about the premises of any other person for the purpose of frightening or intimidating him from doing any lawful act.Violators guilty of a misdemeanor, fined not less than five hundred nor more than one thousand dollars and imprisoned in county jail for twelve months.
Keywords: BRANDISHING